Effects of Growth Retardant on Growth, Flowering and Alkaloid Production in Catharanthus pusillus - Basu, Debjani (Indian Forester, 1992)
This paper deals wilh some investigations on the Catharanthus pusillus plant. These investigations provide some information on the action of growth retardant like CCC at 100 mg/l on the growth and alkaloid production in the plant. Increase in the fresh and dry wights of plants due to increase production of lateral branches. While due to greater assimilation and synthesis of metabolic products the alkaloid synthesis tended to increase which appeared to be beneficial as a result of CCC treatments.